Global, regional, and national time trends in falls and their predictions: an age-period-cohort analysis of the Global Burden of Disease Study 2021 - Huan Jiang; Ning Sun; Huiqi Yang; Ye Li; Ye Li; Lihong Jiang; Huicui Zhao; Yi Zeng; Chengyang Sun; Chun Xu; Yongqiang Lai; Jia Meng (Frontiers in Public Health)
BackgroundFalls are a global public health issue with a heavy disease and socioeconomic burden, with an increasing number of risky people. The aim of this study is to explore the global disease burden of falls and to provide a scientific basis for the prevention and management of falls.MethodsThis study used data from the Global Burden of Disease Study 2021 (GBD 2021) to analyse global, regional, and national temporal trends in falls. An age-period-cohort (APC) model was applied to analyse data from 1990 to 2021, with global predictions made through 2046.FindingsAlthough the falls mortality of all age groups has shown a slight decline globally over the past three decades (Net drift = 0.84%, 95% CI: −0.92, −0.76), the mortality varying across regional and intra-regional levels by sociodemographic index (SDI) quintiles, gender and older adults have not substantially decreased (local drift above 75 years: >0). The APC model reveals that falls mortality has increased with age, especially after the age of 55 years. The period effects shows an overall downward trend (Rate Ratio: 1.08–0.87). The cohort effect shows a trend of increasing first (RR: 1.02–1.18) and then decreasing (RR: 1.18–0.40). The marked heterogeneity in falls mortality is across higher-SDI regions. Population aging is identified as the primary contributor to changes in global falls mortality rates.ConclusionFalls among older adults remain a persistent global issue, with significant regional and intra-regional disparities in falls mortality. These findings underscore the urgent need for age- and region-specific interventions to address this public health challenge.